Abusers gaining custody in family courts: A case series of over turned decisions. Issue 2 (3rd April 2019) - Silberg, Joyanna; Dallam, Stephanie
Abstract: This article presents findings and recommendations based on an in-depth examination of records from 27 custody cases from across the United States. The goal of this case series was to determine why family courts may place children with a parent that the child alleges abused them rather than with the nonoffending parent. We focused on "turned around cases" involving allegations of child abuse that were at first viewed as false and later judged to be valid. The average time a child spent in the court ordered custody of an abusive parent was 3.2 years. In all cases we uncovered the father was the abusive parent and the mother sought to protect their child. Results revealed that initially courts were highly suspicious of mothers' motives for being concerned with abuse. These mothers were often treated poorly and two-thirds of the mothers were pathologized by the court for advocating for the safety of their children. Judges who initially ordered children into custody or visitation with abusive parents relied mainly on reports by custody evaluators and guardians ad litem who mistakenly accused mothers of attempting to alienate their children from the father or having coached the child to falsely report abuse. As a result, 59% of perpetrators were given sole custody and the rest were given joint custody or unsupervised visitation. After failing to be protected in the first custody determination, 88% of children reported new incidents of abuse. The abuse often became increasingly severe and the children's mental and physical health frequently deteriorated. The main reason that cases turned around was because protective parents were able to present compelling evidence of the abuse and back the evidence up with reports by mental health professionals who had specific expertise in child abuse rather than merely custody assessment.